A new side-looking at the dark fermentation of sugarcane vinasse: Improving the carboxylates production in mesophilic EGSB by selection of the hydraulic retention time and substrate concentration. (6th April 2021) - Bernal, Andressa Picionieri; Menezes, Camila Aparecida de; Silva, Edson Luiz
Abstract: In recent years, a lot of scientific effort has been put into reusing the energy potential of sugarcane vinasse by dark fermentation. However, the findings so far indicate that new pathways need to be followed. In this context, this study assessed the effect of hydraulic retention time (HRT, from 24 to 1 h) on vinasse fermentation (10, 20, and 30 g COD L −1 ) in three mesophilic expanded granular sludge bed reactors (EGSB). The carbohydrate conversion remained above 60% at all organic loading rates applied. The maximum hydrogen production rate (8.77 L day −1 L −1 ) was obtained for 720 kg COD m −3 day −1 and associated to the lactate-acetate pathway. The highest productivities of propionic, acetic, and butyric acids were 3.11, 1.68, and 2.45 g L −1 h −1, respectively, at a HRT of 1 h. At this HRT, the degrees of acidification remained between 54% and 76% in all EGSB reactors. This research provides insights for carboxylate production from sugarcane vinasse and suggests applying the EGSB setup in the acidogenic stage of two-stage processes. Graphical abstract: Image 1 Highlights: Dark fermentation of sugarcane vinasse in mesophilic EGSB reactors was assessed. A wide range of organic loading rates has been studied (10 a 720 kg COD m −3 day −1 ). The mesophilic EGSB exhibited higher carboxylate productivity at high OLRs. At OLR of 720 kg COD m −3 day −1 a high degree of acidification was observed. The EGSB reactor is a compelling setup for acidogenesis in two-stage processes.